MENINGKATKAN HASIL BELAJAR SISWA PADA KONSEP GERAK TUMBUHAN MELALUI MODEL INQUIRY TRAINING DI KELAS VIII G SMPN 1 CIJEUNGJING KABUPATEN CIAMIS - Shofiah, Yoyoh (Bioed : Jurnal Pendidikan Biologi, 2019)
The aim of this study is to improve student learning outcomes on the concept of plant motion through inquiry training models. This research is a Classroom Action Research (CAR) carried out in odd semester Academic Year of 2018/2019. The research subjects were class VIII G students of SMP Negeri 1 Cijeungjing, Ciamis Regency with 31 students. The study was conducted in three cycles. Each cycle includes planning, implementation, observation and reflection. Data is collected through tests, and this research is limited only related to cognitive learning outcomes. Based on the results of the study, the value achieved by students in the first cycle was 69.40, the second cycle was 74.30 and the third cycle was 77.44. Based on the setted success indicators that students achieve mastery learning achieve KKM (minimal completeness criteria) value equal to greater than 77.0. The results of this study concluded that the inquiy training model can improve student learning outcomes on the concept of plant movement.